Commemorative plaque laid by Marquis of Ripon - Ghosh, Ayan (Jio Institute, 2023)
The foundation stone for the BMC building was laid on December 19,1884, by the Viceroy, the Marquis of Ripon. The commemorative plaque can be seen inside the BMC building at the entrance lobby. However, work on the site started five years later, on April 25, 1889. After four years of construction, BMC building was finally completed on July 31, 1893.